PengaruhPendidikanKesehatanMetodeRolePlayTerhadapTingkatPerilaku Pencegahan Penularan TB Paru di Poli Klinik RSUDKaranganyar - Sinulingga, Paijah Br (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2024)
Tuberculosis (TB or TBC) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Health Education The Role Playing Method is a way of dramatizing behavior in relation to social problems with the aim that students can appreciate and appreciate the feelings of others. The purpose of this study was to determine the effect of providing health education using the role play method on TB transmission prevention behavior at the Karanganyar Hospital Polyclinic. This study used a quasi-experimental design method with pre and post test with control design, the number of respondents in this study was 30 people divided into two groups, each group consisting of 15 people, the sampling technique used consecutive sampling. The research instrument used a questionnaire, and data analysis used the Mann Whitney test. The results showed that health education through role play had an effect on the knowledge, attitudes and behavior of patients regarding the prevention of pulmonary TB transmission in the Karanganyar Hospital Polyclinic with rescpective significance of 0,002, 0,001, 0,001.